PUTRACOM: a formalism of a novel component model - Nejati, Faranak; Ng, Keng Yap; Abd Ghani, Abdul Azim; Jaafar, Azmi (INSIGHT, 2020)
The composition mechanisms and interactions of current component models are mostly base on port or function calls from other components. However, in both styles, the number of interactions that depend on the number of ports and method calls may increase dramatically. Hence, to avoid such complexity of composing components and coordination of the interaction among them, a component model and policy to provide a separation between the components and coordinating is needed. This study presents a formal specification of a novel component model for discrete-event and non-blocking component-based systems called PUTRACOM. A new component model, named PUTRACOM is presented in this paper. PUTRACOM supports to develop concurrent software systems with discrete-event. PUTRACOM defines components by two essential features; they are the Observer/Observable unit and a computation unit. These two features allow a component to have fixed behavior without any dependency on other components. The components can be composed using a well-defined set of connectors. PUTRACOM has been formally defined based on the well-defined and sound methods like CSP and RTSs. PUTRACOM provides a way to construct components and coordinate them with a well-founded mechanism. The model defines a set of exogenous connectors and an observer/observable unit to encapsulate components and coordination. In order to illustrate the way of component composition in the proposed model, an example of the control system of a refrigerator is used. Moreover, to evaluate its applicability, the example has been implemented in Colored Petri Net (CPN) tools.